2017
DOI: 10.1038/s41598-017-14778-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Study of Idiopathic Osteonecrosis of the Femoral Head

Abstract: Idiopathic osteonecrosis of the femoral head (IONFH) is an ischemic disorder that causes bone necrosis of the femoral head, resulting in hip joint dysfunction. IONFH is a polygenic disease and steroid and alcohol have already known to increase its risk; however, the mechanism of IONFH remains to be elucidated. We performed a genome-wide association study using ~60,000 subjects and found two novel loci on chromosome 20q12 and 12q24. Big data analyses identified LINC01370 as a candidate susceptibility gene in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…An essential facet of executive control is response inhibition, which enables the suppression of inappropriate or no-longer relevant actions [ 43 , 44 ] and is facilitated through prefrontal cortical regions, including the inferior frontal gyrus (IFG) and the DLPFC [ 44 ]. Previous studies have observed sex-related differences in inhibition ability [ 6 , 26 29 , 45 ]. We have previously demonstrated in the context of the Stop-Signal Task that following practice, females learned to improve their response inhibition ability to a greater extent than males [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…An essential facet of executive control is response inhibition, which enables the suppression of inappropriate or no-longer relevant actions [ 43 , 44 ] and is facilitated through prefrontal cortical regions, including the inferior frontal gyrus (IFG) and the DLPFC [ 44 ]. Previous studies have observed sex-related differences in inhibition ability [ 6 , 26 29 , 45 ]. We have previously demonstrated in the context of the Stop-Signal Task that following practice, females learned to improve their response inhibition ability to a greater extent than males [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies of selected populations have identified several loci of interest, including clusters of variants near glutamate receptor genes in patients with ALL, 45 corticosteroid-induced osteonecrosis, 33 and several loci of unknown significance, which may be related to coagulation pathways, lipid metabolism, or alcohol drinking behavior. 46 …”
Section: Pathophysiology and Pathogenesismentioning
confidence: 99%
“…Moreover, a recent genome-wide association study from Japan identified long intergenic non-protein coding RNA 1370 (LINC01370) as a candidate risk gene in Japanese patients who have idiopathic ONFH, and stratified their analysis by risk factors suggested that the 12q24 locus was associated with the disease through drinking capacity. 60 …”
Section: Current Concepts Concerning the Pathogenesis Of Onfhmentioning
confidence: 99%